Demanda y oferta de semillas de maíz (Zea mays L.) y los factores que influyen en la diversidad de variedades entre los agricultores de Sahbacá y Yaxcabá, Yucatán - Pool Pérez, Maria José (Universidad Autónoma de Yucatán, Facultad de Medicina Veterinaria y Zootecnia, México, 2007)
The table of contents for this item can be shared with the requester. The requester may then choose one chapter, up to 10% of the item, as per the Fair Dealing provision of the Canadian Copyright Act Traditional and small-scale agriculture in Yucatan requires campesinos´decision making on which and how many varieties they will plant, where each of these will be seeded and what management practices during the cultivation as well as post harvesting. The objectives of this study were: to describe the mechanism of interchanged and marketing of seeds pool, as well as, to evaluate the factors that affect campesinos’ decision making on conservation of corn diversity in the communities of Yaxcaba and Sahcaba, Yucatan. In Sahcaba eight varieties were found from the types known as: X’mejen nal, Xnuk-nal and one introduced variety locally known as white hybrid. In Yaxcaba 18 local varieties were identified: Nal t’eel, X’ mejen-nal, X-nuuk-nal and several introduced varieties such as: Yellow and white hybrids, and a combination of these previous; Nalxoy and improved yellow corn. There is an informal market of seeds in both communities, interchange between producers is common between campesinos of the same community, as well as, between near by communities without the intervention of official institutions or seed distributors. Most of the interchange doesn’t involve currency and this seed system is an strategy of access to local corn varieties. Through an analysis of multiple regression in Sahcaba were identifies the most important factors that affect the seed pool diversity such as: available hand labor, number of plots, experience index, family size and total area cultivated. Furthermore, most important seed pool attributes for campesinos in Sahcaba are the agronomic (potential yield, pest and disease resistance and drought resistance among others). According to local preference and management the tree varieties preferred are: white and yellow Xnul-nal, and white hybrid. In contrast, for Yaxcaba the most important ...